Assessment of indoor thermal environment of Aceh house based on WBGT index. Issue 1 (November 2021) - Muslimsyah,; Munir, A; Away, Y; Abdullah,; Huda, K; Salsabilah, M
Abstract: Thermal comfort is one of the standard assessments of building thermal environment. Air movement is an important parameter for in a naturally ventilated to achieve thermal comfort by accelerating the evaporative cooling process on the human body. Aceh House has a standard of thermal comfort with a vernacular architecture with a natural ventilation system. This vernacular architectural building has a fairly high harmonization of the environment because it has undergone a process of adaptation. In this study, observations were made at the Original House (OH), the Adaptive Reuse House (ARH), and the Aceh Modified House (AMH). By using the method of assessing changes in environmental comfort, using Wet Bulb Temperature Index (WBGT) method, the minimum and maximum temperature ranges are 25°C and 30°C. In the WBGT thermal rating, AMH has the higher thermal and is followed by ARH and OH respectively. Thus, OH has lower thermal compared to other Aceh houses.